The Cyclical Component of the Debt Brake — Leeway and Limits - Stefan Korioth; Michael W. Müller (Wirtschaftsdienst)
Abstract This article discusses the constitutional framework for reforming the cyclical component of the debt brake in Germany. This component takes cyclical developments into account when determining the permissible level of public debt. When designing the cyclical component, a variety of judgments must be made to determine the normal cyclical situation, especially with regard to the compatibility of family and work, the extent of part-time work and the retirement age. The parliamentary legislature, which enjoys considerable leeway, should make these decisions.